2021
DOI: 10.1021/acsbiomaterials.1c00386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Assisted 3D Model to Investigate the Osteoinductive Potential of MC3T3-Derived Extracellular Vesicles

Abstract: Effective and rapid regeneration of bone defects often pose substantial challenges in severe accidental injuries and disabilities occurring due to diseases and/or advanced age, especially in patients having reduced tissue regeneration competence. The success of mesenchymal stromal cell (MSC)-based research strategies in improving bone regeneration was hampered not only due to the limited knowledge of therapeutic actions of MSCs but also due to difficulties as well as expenses related to cell manufacturing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…There is a growing body of evidence demonstrating the delivery of EV-functionalised biomaterials to promote bone regeneration [ 84 , 85 ], however, the vehicle employed often does not support EV-induced tissue regeneration. For example, Holkar et al reported the potential of an alginate hydrogel loaded with osteoblasts and their EVs for bone tissue engineering applications [ 85 ], however, alginate itself is osteogenically inert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence demonstrating the delivery of EV-functionalised biomaterials to promote bone regeneration [ 84 , 85 ], however, the vehicle employed often does not support EV-induced tissue regeneration. For example, Holkar et al reported the potential of an alginate hydrogel loaded with osteoblasts and their EVs for bone tissue engineering applications [ 85 ], however, alginate itself is osteogenically inert.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence demonstrating the delivery of EV-functionalised biomaterials to promote bone regeneration [ 84 , 85 ], however, the vehicle employed often does not support EV-induced tissue regeneration. For example, Holkar et al reported the potential of an alginate hydrogel loaded with osteoblasts and their EVs for bone tissue engineering applications [ 85 ], however, alginate itself is osteogenically inert. The importance of the delivery vehicle on EV functionality was demonstrated by Davies et al, where osteoblast-derived EVs exhibited substantially enhanced mineralisation potency when delivered in mineralising medium compared to non-mineralising medium [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, 3D culture technology can be broadly divided into two types: material-free cultures (cell spheres formed by aggregation of cells) and material-supported cultures. Material-free 3D culture methods mainly include 3D spherical spatial boundary conditions [ 54 ], scaffold-free suspension cultures [ 55 ], systematic microcarrier screening, hydrogel-assisted 3D culture [ 56 , 57 ], and agitated culture conditions [ 58 ]. Material-supported culture methods are relatively diverse, including fibrous scaffolds [ 59 ], native extracellular matrix (ECM) bioscaffolds [ 60 ], hollow fiber bioreactors [ 61 ], quantum cell expansion systems [ 62 ], and computer-controlled bioreactors [ 63 ].…”
Section: Extracellular Environment Preconditioningmentioning
confidence: 99%
“…Hydrogels provide a 3D matrix for Exos that prevents the dispersion of Exos and maintains its local concentration, which enables controlled release of Exos for sustained efficacy. Hydrogel-released Exos at bone defect sites can reduce Exos consumption and ectopic effects to promote angiogenesis and osteogenesis [ 61 ]. Some scholars found gelatin nanoparticle hydrogels combined with hADSC-Exos can accurately transport the hADSC-Exos to the target site and effectively promote bone healing [ 62 ].…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%
“…Yu et al [ 4 ] demonstrated that Exos derived from periodontal ligament stem cells (PDLSCs) encapsulated in a hydrogel 3D microenvironment exhibited enhanced osteoinductive ability and could significantly promote bone defect repair in rats. Another study demonstrated alginate hydrogels combined with EVs showed increased interactions with other cells, cell aggregation, and prolonged long-term viability, which in turn promoted osteogenesis [ 61 ]. Therefore, a variety of special properties of hydrogels can be combined with MSC-EVs to effectively treat bone defects.…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%